Optimization of Basket Oven Oil Seal Design For Quality, Productivity and Material Handling - Gofur, Muhamad; Sarjono, Sarjono; Saputra, Dafid Mega; Apriani, Ades Yulia (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
In the oil seal production process, one of them is the post-cure oven process as a heat treatment to engineer the rubber material so that it has resistance to friction and has high heat resistance. The post-cure oven process itself uses equipment in the form of an oven basket made of heat-resistant steel material to place the oil seal. However, the Basket oven itself has a maximum limit for placing the oil seal in the oven, so calculations are needed to find the optimization value to find out the maximum value obtained so as to increase work productivity. From the problems found, the existing oven baskets were unable to accommodate 1,442 pcs/lot of products, but were only able to accommodate 1,344 pcs of products. so it is necessary to design a new basket oven to get the optimal value so that the basket oven can accommodate as many as 1,442 pcs/lot of products. From the research results it is known that to save material the most optimum cutting value is if the value of x = 8.5. Meanwhile, to get the maximum volume value, it is cut with a value of x = 11. By using the new oven basket, the product volume that can be accommodated is 1,568 pcs when compared to the use of the old basket which was previously able to accommodate 1,344 pcs of product. The use of a new basket oven can increase basket volume by 16.7%.